Pretreatment plasma fibrinogen and serum albumin levels predict therapeutic efficacy of concurrent radiochemotherapy for esophageal squamous cell cancer - Wang, Jijin; Huang, Di; Wang, Yuanyuan; Yuan, Qianqian; Chen, Xue; Cheng, Yufeng (Frontiers in Oncology, 2022)
Purpose Evidence implies that plasma fibrinogen and serum albumin level (FA score) based on plasma fibrinogen and serum albumin is related to cancer prognosis. However, the association between the FA score and therapeutic efficacy of concurrent radiochemotherapy in esophageal squamous cell carcinoma (ESCC) has not yet been evaluated. This study aimed to assess the role of pretreatment FA score in predicting the therapeutic efficacy of concurrent radiochemotherapy for patients with esophageal squamous cell cancer. Methods This retrospective study evaluated 154 patients with ESCC who underwent concurrent radiochemotherapy. Receiver operating characteristic curve (ROC) analysis was used to determine the appropriate cut-off values, and multivariate analysis and Kaplan-Meier curve were used to evaluate prognosis. Results FA score was significantly associated with the N stage and M stage (P = 0.015 and 0.042, respectively). Chi-square analysis/Fisher’s exact tests revealed a correlation between the FA score and curative effect (P < 0.001), and higher FA score was associated with poorer treatment effect. Multivariate analysis indicated that FA score (P < 0.001) was predictor of overall survival (OS). Kaplan-Meier curve demonstrated that pretreatment FA score was significantly associated with the OS of ESCC: Patient with higher FA score has lower median OS. Conclusions The FA score is a reliable prognostic predictor that could assess the curative effect and OS benefit of concurrent radiochemotherapy in patients with ESCC.